Involvement of cholesterol in Campylobacter jejuni cytolethal distending toxin-induced pathogenesis. (April 2015) - Lai, Cheng-Kuo; Su, Jing-Chi; Lin, Yu-Hsin; Chang, Chia-Shuo; Feng, Chun-Lung; Lin, Hwai-Jeng; Lin, Chun-Jung; Tseng, Guan-Chin; Liu, Hsin-Ho; Hsieh, Jer-Tsong; Su, Hong-Lin; Lai, Chih-Ho
ABSTRACT : Aim: The aim of this study was to investigate whether cholesterol plays a pivotal role in cytolethal distending toxin (CDT) mediated pathogenic effects in hosts.Materials & methods: The molecular mechanisms underlying cholesterol sequestering conferred resistance to CDT-induced DNA double-strand breaks (DSBs) and cell cycle arrest were investigated. Histopathological analysis was conducted for evaluating CDT-induced intestinal inflammation in mouse.Results: CDT actions were attenuated by treatment of cells with methyl-β-cyclodextrin (MβCD). Severe intestinal inflammation induced by CDT treatment was observed in high-cholesterol diet-fed mice, but not in normal diet-fed mice, indicating that cholesterol is essential for CDT intoxication.Conclusion: Our findings demonstrate a molecular link between Campylobacter jejuni CDT and cholesterol, which is crucial to facilitate CDT-induced pathogenesis in hosts.